2021
DOI: 10.1002/ptr.7349
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antiinfective effect of caffeine in a mouse model of disseminated salmonellosis

Abstract: Caffeine has been reported for its antiinflammatory properties by stimulating phagocytosis. In this study, we investigated the antiinflammatory and antiinfective potential of caffeine in murine macrophage cell cultures and Swiss mice infected with virulent Salmonella enterica serotype typhimurium. Peritoneal macrophages (pMØ) were treated with caffeine on 96-well plates for 24 hr and then infected with Salmonella for 4 hr. In another experiment, the pMØ were first infected with the bacterium for 4 hr and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Caffeine reduces intrahepatic lipid content by stimulating β-oxidation and autophagy-lysosomal pathways [70] . And in a mouse model of disseminated salmonellosis, caffeine also has anti-inflammatory and anti-infective effects [71] . Melanin has a strong ROS scavenging ability and can promote the polarization of macrophages for cardiac repair [72] .…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine reduces intrahepatic lipid content by stimulating β-oxidation and autophagy-lysosomal pathways [70] . And in a mouse model of disseminated salmonellosis, caffeine also has anti-inflammatory and anti-infective effects [71] . Melanin has a strong ROS scavenging ability and can promote the polarization of macrophages for cardiac repair [72] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of TNF-α, IL-1β, IL-6, and inducible nitric oxide synthase was found to be down-regulated in caffeine-treated mice after infection, suggesting that caffeine can be used in combination with antibiotics for treatment of bacterial infections. 64 New studies have found that prenatal exposure of 80 mg/kg caffeine can significantly reduce the average body weight of rat offspring before weaning, which may be related to the immune dysfunction in rats caused by excessive caffeine exposure; however, 100 mg/kg caffeine body weight does not cause neurobehavioral toxicity in adult mice. 65 The results suggest that excessive caffeine exposure may lead to immune dysfunction and intrauterine growth restriction retardation in pregnant women, and coffee consumption before and during pregnancy is not recommended.…”
Section: Animal Experimentsmentioning
confidence: 99%